THE OPTIMIZATION OF ONLINE SELLING THROUGH WEBSITE-BASED E-COMMERCE APPLICATIONS AND MOBILE APPLICATIONS FOR MSMES - Chandra Jaya, Rama; Kosadi, Ferry (Inaba of Community Services Journal, 2022)
The challenges of MSMEs in the digital era through the use of digital platforms in transactions are an excellent opportunity to expand marketing which is expected to increase sales revenue. The digital platform in the form of a marketplace provides various features that can be utilized by MSMEs in the form of online shop features, product promotions, product management and delivery services as well as various payment features that provide convenience and convenience for customers to shop. However, not all MSME actors are able to take advantage of various features in the marketplace with various obstacles faced by MSMEs, including a lack of understanding of the various features available and the benefits that will be obtained as well as a reluctance to learn and operate the various features provided both on the website platform and those that are available. is mobile. The purpose of socializing the use of websites and mobile commerce is expected to help increase market expansion and increase sales revenue as well as increase digital literacy from MSMEs. The method used is through counseling and training as well as the practice of using various features available on the marketplace including product management and packaging and promotion. Further processes, especially those related to increasing income and financial management, are still needed in the utilization of this website and mobile commerce.